Avaliação da arquitetura óssea trabecular por meio de processamento de imagem digital em radiografias panorâmicas - Klein, Caroline Gugisch (2005)
The purpose of the present work was to modify a skeletonization algorithm and to create an algorithm to quantify radiographic images. A panoramic radiographic digital treatment of 50 volunteers diagnosed as otheoporotics and non-ostheoporotics in a previous work was done. In order to verify the validity of the digital resource, a questionnaire was elaborated that along with the radiographies was distributed among 15 radiologists. The examiners analyzed in a subjective way 99 images, responding which criteria were adopted for the evaluation of the trabecular bone architecture. The data obtained in the applied questionnaire and in the digital image treatment were submitted to a descriptive analysis in order to verify the agreement in the diagnostic hypothesis and to define a golden standard. A ROC curve was built to check the cut point and to establish which Gauss filter was the best, with a variable ratio of 30, 35, 40, 45, or 50. The ratio 30 filter was chosen since it presented the best specificity (94.3%), even having a low sensibility (50%). The agreement levels among the examiners were below 80%. However a high significance among the percentage of black points was registered (p<0.001). The method of image processing trough the skeletonization in panoramic radiographies can become a valuable support for the dentist-surgeons.